Pengaruh Kualitas Pelayanan, Lokasi dan Word of Mouth Terhadap Sales UMKM Seblak Gurilem Tangerang Selatan - Muhammad Raffli Arya Nugroho; Budi Santosa Kramadibrata (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Micro Small and Medium Enterprises have an important role in supporting the regional and national economy. Seblak Gurilem, one of the Micro Small and Medium Enterprises in South Tangerang, faces challenges in maintaining competitiveness in the midst of intense competition in the culinary business. This study aims to analyze the effect of service quality, location, and word of mouth on sales. The research method used is quantitative with a causal associative approach. Data was collected through a questionnaire involving 100 respondents who are Seblak Gurilem consumers. Data analysis was carried out using multiple linear regression. The results showed that service quality and word of mouth have a positive and significant effect on sales, while location has no significant effect. The implications of this study provide recommendations for culinary businesses to improve service quality and utilize word of mouth strategies to attract more customers and maintain consumer loyalty.